2022
DOI: 10.1186/s12951-022-01732-y
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN4-positive migrasome derived from retinal pigmented epithelium cells contributes to the development of proliferative vitreoretinopathy

Abstract: Background Proliferative vitreoretinopathy (PVR) is a blind-causing disease initiated by the activation of retinal pigmented epithelium (RPE) primarily induced by TGF-β families. Migrasome is a recently discovered type of extracellular vesicle related to cell migration. Results Here, we used ex vivo, in vitro, and in vivo models, to investigate the characteristics and functions of migrasomes in RPE activation and PVR development. Results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…Imaging and Biochemical data (Ding et al 2023 ; Huang et al 2019 ; Jiang et al 2019 ; Jiao et al 2021 ; Liang et al 2023 ; Ma et al 2015 ; Wu et al 2017 , 2022 ; Zhang et al 2022 ; Zhao et al 2019 )…”
Section: Step-by-step Proceduresunclassified
See 1 more Smart Citation
“…Imaging and Biochemical data (Ding et al 2023 ; Huang et al 2019 ; Jiang et al 2019 ; Jiao et al 2021 ; Liang et al 2023 ; Ma et al 2015 ; Wu et al 2017 , 2022 ; Zhang et al 2022 ; Zhao et al 2019 )…”
Section: Step-by-step Proceduresunclassified
“…Additionally, Migrasomes are excessively generated by macrophage lineage cells upon amyloid protein stimulation, thereby contributing to complement-dependent blood vessel damage (Hu et al 2023 ). Furthermore, it has been discovered that Migrasomes derived from Pigmented epithelium cells promote the progression of proliferative vitreoretinopathy (Wu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Retinal pigmented epithelium (RPE) activated by cytokines can lead to proliferative vitreoretinopathy (PVR), causing retinal detachment and blindness [ 43 , 44 ]. Wu et al [ 45 ] found that human PVR samples express the migrasome marker, TSPAN4. RPE from Norway rat activated by TGF-β1 increases TSPAN4 expression and produces migrasomes.…”
Section: Migrasomes Mediate the Pathological Process Of Diseasesmentioning
confidence: 99%
“…Migrasomes can be internalized by retinal pigmented epithelium (RPE), promoting RPE activation and proliferative vitreoretinopathy (PVR) progression by increasing the migration and proliferation ability of RPE [59]. TSPAN4 is abundant in the migrasome membrane and is one of the most effective tetraspanins for migrasome induction [46], stabilizing the migrasome structure and acting as a migrasome marker [6,60].…”
Section: Migrasomes In Diseasesmentioning
confidence: 99%
“…Moreover, neurons are found in close vicinity to migrasomes, and double immunofluorescent staining revealed co-localization of microglia migrasomes and neuron fragments, suggesting a potential interaction between the migrasomes and surrounding neurons [ 40 ]. Migrasomes can be internalized by retinal pigmented epithelium (RPE), promoting RPE activation and proliferative vitreoretinopathy (PVR) progression by increasing the migration and proliferation ability of RPE [ 59 ]. TSPAN4 is abundant in the migrasome membrane and is one of the most effective tetraspanins for migrasome induction [ 46 ], stabilizing the migrasome structure and acting as a migrasome marker [ 6 , 60 ].…”
Section: Migrasomes In Diseasesmentioning
confidence: 99%